Planificación de la expansión de la transmisión del sistema eléctrico ecuatoriano considerando repotenciación y reconfiguración de la red. - Ñacato Ibarra, Kevin Josue (2023)
In this research, the reconfiguration and repowering model is implemented to solve the transmission network expansion problem to satisfy the future demand for electric energy of the National Interconnected System of Ecuador. This model's application is carried out using the mathematical modeling language AMPL. First, the Garver 6-bus test system (Garver_6Bus) is taken as a case study to verify the model's performance proposed in previous work. Then, the Ecuadorian electrical system called SNI_45Bus is used as a case study. A system validated in DigSILENT PowerFactory software is used to obtain the input parameters of the optimization problem. Then, cost estimation is performed to obtain an approximation of the investment required to build the new transmission lines and thus obtain a solution to the expansion problem at a minimum cost. Finally, the results obtained for three study cases are analyzed: repowering, reconfiguration, and a combination of repowering with reconfiguration. The results show that the investment costs for the solution to the network expansion problem are lower if only the repowering of the existing transmission system is considered.